2017
DOI: 10.2147/ndt.s149712
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum uric acid and total bilirubin in elderly patients with major postischemic stroke depression

et al.

Abstract: BackgroundThis was a longitudinal study which investigated the relationship between serum uric acid (SUA) and total bilirubin (Tbil) upon admission in elderly stroke patients and the occurrence of postischemic stroke depression (IPSD) at 3, 6, and 9 months of post-stroke follow-up.Subjects and methodsData were analyzed for 525 acute ischemic stroke patients. Beck Depression Inventory (BDI) scores >17 and Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) were used separately to scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
3
21
1
Order By: Relevance
“…Previous study has reported the higher levels of SUA on admission was associated with the occurrence of 3-month major PSD, while lower level of SUA on admission was closely related to the occurrence of major PSD between 3-and 6month post-stroke. Six months after acute ischemic stroke, there was no relationship between major PSD and baseline SUA (15). The differences in time of assessment and diagnosis, subjects' samples, and psychiatric assessment methods could explain the discrepancies between our study and their findings.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Previous study has reported the higher levels of SUA on admission was associated with the occurrence of 3-month major PSD, while lower level of SUA on admission was closely related to the occurrence of major PSD between 3-and 6month post-stroke. Six months after acute ischemic stroke, there was no relationship between major PSD and baseline SUA (15). The differences in time of assessment and diagnosis, subjects' samples, and psychiatric assessment methods could explain the discrepancies between our study and their findings.…”
Section: Discussioncontrasting
confidence: 80%
“…In recent years, the interest of psychiatrist in the association between oxidative stress and depression has grown stronger and relevant studies have shown that the depression is accompanied by increased oxidative stress and decreased antioxidant defenses (24,25). Unlike previous studies, the present investigation focused on the occurrence of PSD at discharge and attempted to link this outcome with SUA levels on admission (15). Our study may provide an effective biomarker for psychiatrists to diagnose PSD at discharge.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Because of the high metabolic and low antioxidant characteristics of the brain, oxidative and nitrosative stress pathways are considered the most crucial pathophysiological factors [23]. Bilirubin, as the final metabolite of hemoglobin, is a strong antioxidant, but also has neurotoxicity and can easily spread through the blood-brain barrier [24]. Unconjugated bilirubin has been proved to cause neurotoxicity and brain cell death [25].…”
Section: Discussionmentioning
confidence: 99%